Usefulness And Effectiveness Of Locally Available Food That Can Improve Gut Flora Using Mhealth Among Malnourished Nomadic Tribe Children Of Sikar, Rajasthan: Protocol For A Randomized Control Trial (International Journal of Food and Nutritional Sciences, 2022)
BackgroundGut microbes help in the absorption of nutrients in food, and poor gut health can impact the growth and development of children. In addition, poverty and poor sanitation practices enable high rates of enteric infections. As a result, diarrhea remains unabated in the lower economy sections. Mothers' awareness regarding the gut health issues of their children via mHeatlh (mobile audio messages) can be one of the many ways to strengthen gut health issues among children.ObjectiveThe study objective is to design, develop and evaluate mHealth intervention to improve gut health among the tribal community of Sikar district of Rajasthan through a randomized control trial.MethodsA randomized control trial study will be conducted with 300 participants from nomadic tribes (Banjara, Luharu, Sapera) of Sikar, Rajasthan. Eligible participants include mothers of 6 months to 5 years old malnourished children, those who agreed to participate in the study, are available for follow-up interviews, and have at least a basic phone. The malnutrition status of the children will be determined via WHO Z-Score. The mothers of the participant children will be randomized into the following two groups: the intervention group (pre-recorded mobile-based audio messages) and the control group (paper-based one-time message booklet). Study participants in the intervention group will receive a daily automated system-generated recorded message via phone call. Control group participants will be provided with a paper-based booklet. Follow-up visits will be conducted at 3 and 6 months from the baseline in both groups. Differences in diarrheal episodes, knowledge, attitudes, and practices of mothers will be measured across the groups.ResultsDescriptive analysis of the gathered data will be performed using SAS v9.1. Results will be reported at 95% CI and P